Population pharmacokinetics of mefloquine in patients with acute falciparum malaria. - Simpson, J; Price, R; ter Kuile, F; Teja-Isavatharm, P; Nosten, F; Chongsuphajaisiddhi, T; Looareesuwan, S; Aarons, L; White, N (1999)
OBJECTIVE: To construct a population pharmacokinetic model for mefloquine in the treatment of falciparum malaria. BACKGROUND: Mefloquine is the treatment of choice for multidrug-resistant falciparum malaria. The factors that influence the pharmacokinetic properties of mefloquine in acute malaria are not well characterized. METHODS: The pharmacokinetic properties of mefloquine were evaluated in 257 patients with acute falciparum malaria by use of nonlinear mixed-effects modeling. Two different oral dose regimens were used: (1) a split dose of 15 mg base/kg initially followed by 10 mg/kg 24 hours later (n = 159) and (2) a single dose of 25 mg/kg (n = 98). Mefloquine was combined with artesunate in 105 (41%) patients (74 received a split dose and 31 received a single dose). RESULTS: Splitting the mefloquine dose increased the area under the concentration-time curve [AUC(0-infinity)] by 50% (95% confidence interval [CI], 36% to 65%) for monotherapy and by 20% (95% CI, 3% to 40%) for combined therapy. The apparent volume of distribution (V/F) was significantly lower in patients receiving split doses of mefloquine monotherapy (mean, 8.14 L/kg; 95% CI, 7.49 to 8.86 L/kg) compared with a single dose (mean, 20.37 L/kg; 95% CI, 16.26 to 25.51 L/kg). Patients who received mefloquine monotherapy and cleared parasitemia in less than 48 hours had a significantly higher AUC(0-infinity) independent of any confounders, compared with patients with slower parasite clearance (geometric mean [95% CI], 50,373 ng/mL x day [46,121 to 55,017 ng/mL x day] versus 45,583 ng/mL x day [42,306 to 49,125 ng/mL x day]). CONCLUSIONS: The pharmacokinetic properties of mefloquine in malaria were relatively unaffected by demographic variables (other than body weight) or disease severity. If it is assumed that apparent clearance and volume of distribution are unaffected by dose regimen, then splitting the 25 mg/kg mefloquine dose improves oral bioavailability and the therapeutic response in the treatment of acute falciparum malaria.